KEMAMPUAN DAN KEKUATAN BIOREMEDIASI AGEN HAYATI JAMUR FUNGI PELAPUK PUTIH - dkk, Donawati (BPPT)
Indonesia is a tropical country and the richest country in the world for biodiversity, including fl ora and fauna, invertebrates, phytoplankton, bacteria, and huge number of fungus such as mushrooms, molds, mildews and smuts. White rot fungi is one of the ubiquitous creatures in Indonesia. Results indicated that white rot fungus has ability to degrade successfully some organic pollutansin the environment, such as polycyclic aromatic hydrocarbons (PAH), Polychlorinated Biphenyls (PCB?s), Trinitrotoluence (TNT), and DDT. This organism has ability to release intra and extra-cellular enzymes. There are three important rules in these degradation processes, called lignin modifi ed enzymes (LME?s) including Lignin peroxidase, Mn-dependent peroxidase and Laccase. White rot fungi contains all three enzymes and able to breakdown and mineralize several environmental pollutants into non toxic forms. This paper discuss several processes responsible for this degradation.Key words: White rot fungi, bioremediation, lignin modifi ed enzymes, persistent organic pollutants.